(untitled) (INTERNATIONAL CONFERENCE OF NATURAL AND SOCIAL-HUMANITARIAN SCIENCES, 2024)
We know that the formation of social skills among schoolchildren in our country is one of the most urgent problems. In this thesis, we talk about the content of forming social skills in elementary school students.